Biogenic oxidized organic functional groups in aerosol particles from a mountain forest site and their similarities to laboratory chamber products - Schwartz, R. E.; Russell, L. M.; Sjostedt, S J; Vlasenko, A.; Slowik, J. G.; Abbatt, J. P. D.; Macdonald, A. M.; Li, S. M.; Liggio, J.; Toom-Sauntry, D.; Leaitch, W. R. (ATMOSPHERIC CHEMISTRY AND PHYSICS, 2010)
Submicron particles collected at Whistler, British Columbia, at 1020 m a.s.l. during May and June 2008 on Teflon filters were analyzed by Fourier transform infrared (FTIR) and X-ray fluorescence (XRF) techniques for organic functional groups (OFG) and elemental composition. Organic mass (OM) concentrations ranged from less than 0.5 to 3.1 mu g m(-3), with a project mean and standard deviation of 1.3 +/- 1.0 mu g m(-3) and 0.21 +/- 0.16 mu g m(-3) for OM and sulfate, respectively. On average, organic hydroxyl, alkane, and carboxylic acid groups represented 34%, 33%, and 23% of OM, respectively. Ketone, amine and organosulfate groups constituted 6%, 5%, and <1% of the average organic aerosol composition, respectively. Measurements of volatile organic compounds (VOC), including isoprene and monoterpenes from biogenic VOC (BVOC) emissions and their oxidation products (methyl-vinylketone/methacrolein, MVK/MACR), were made using co-located proton transfer reaction mass spectrometry (PTR-MS). We present chemically-specific evidence of OFG associated with BVOC emissions. Positive matrix factorization (PMF) analysis attributed 65% of the campaign OM to biogenic sources, based on the correlations of one factor to monoterpenes and MVK/MACR. The remaining fraction was attributed to anthropogenic sources based on a correlation to sulfate. The functional group composition of the biogenic factor (consisting of 32% alkane, 25% carboxylic acid, 21% organic hydroxyl, 16% ketone, and 6% amine groups) was similar to that of secondary organic aerosol (SOA) reported from the oxidation of BVOCs in laboratory chamber studies, providing evidence that the magnitude and chemical composition of biogenic SOA simulated in the laboratory is similar to that found in actual atmospheric conditions. The biogenic factor OM is also correlated to dust elements, indicating that dust may act as a non-acidic SOA sink. This role is supported by the organic functional group composition and morphology of single particles, which were analyzed by scanning transmission X-ray microscopy near edge X-ray absorption fine structure (STXM-NEXAFS).